DECISION SUPPORT SYSTEM FOR SELECTING MOBILE LEGENDS HEROES IN EPIC TIER USING AHP-TOPSIS METHOD - Akhmad Zaenal Abidin; Muhammad Fairuzabadi; Wibawa (JTH: Journal of Technology and Health, 2024)
The Mobile Legends game is a Multiplayer Online Battle Arena (MOBA) game designed specifically for mobile phones, though it can also be played on PCs. The game features various roles that players must fill, each with distinct tasks and responsibilities. Not all Mobile Legends players are familiar with these roles, which include core/jungler, roaming, gold lane, mid lane, and exp lane. Choosing heroes in the Epic tier often makes it difficult for players to advance in rank. This tier is considered notoriously challenging by Mobile Legends players because at the season reset, rankings drop from Epic II, Legend, Mythic, and Mythical Glory to Epic V or Epic II. Given these challenges, the author has titled their work "Decision Support System for Selection of Mobile Legends Heroes in Epic Tier Using the AHP Method". This system uses the hybrid AHP-TOPSIS method and is developed using the waterfall model, including tools like Flowcharts, Context Diagrams, Data Flow Diagrams level 1, Entity Relationship Diagrams, Table Relations, Table Specifications, and uses the Visual Code application with MySQL as the database. The aim is to provide a practical solution through a computer-based decision support system. This system is intended to assist players in selecting the most suitable Mobile Legends heroes for the Epic Tier, based on specific criteria and roles.